Electrospun Nanofiber Meshes With Endometrial MSCs Modulate Foreign Body Response by Increased Angiogenesis, Matrix Synthesis, and Anti-Inflammatory Gene Expression in Mice: Implication in Pelvic Floor - Mukherjee, Shayanti; Darzi, Saeedeh; Paul, Kallyanashis; Cousins, Fiona L.; Werkmeister, Jerome A.; Gargett, Caroline E. (Frontiers in Pharmacology, 2020)
PURPOSE: Transvaginal meshes for the treatment of Pelvic Organ Prolapse (POP) have been associated with severe adverse events and have been banned for clinical use in many countries. We recently reported the design of degradable poly (L-lactic acid)-co-poly (-caprolactone) nanofibrous mesh (P nanomesh) bioengineered with endometrial mesenchymal stem/stromal cells (eMSC) for POP repair. We showed that such bioengineered meshes had high tissue integration as well as immunomodulatory effects in vivo. This study aimed to determine the key molecular players enabling eMSC- based foreign body response modulation. METHODS: SUSD2+ eMSC were purified from single cell suspensions obtained from endometrial biopsies from cycling women by magnetic bead sorting. Electrospun P nanomeshes with and without eMSC were implanted in a NSG mouse skin wound repair model for 1 and 6 weeks. Quantitative PCR was used to assess the expression of extracellular matrix (ECM), cell adhesion, angiogenesis and inflammation genes as log2 fold changes compared to sham controls. Histology and immunostaining was used to visualize the ECM, blood vessels and multinucleated foreign body giant cells around implants. RESULTS: Bioengineered P nanomesh/ eMSC constructs explanted after 6 weeks showed a significant increase in 35 genes associated with ECM, ECM regulation, cell adhesion angiogenesis and immune response in comparison to P nanomesh alone. In the absence of eMSC, acute inflammatory genes were significantly elevated at 1 week. However, in the presence of eMSC, there was an increased expression of anti-inflammatory genes including Mrc1 and Arg1 by 6 weeks. There was formation of multinucleated foreign body giant cells around both implants at 6 weeks that expressed CD206, a M2 macrophage marker. CONCLUSION: This study reveals that eMSC modulate the foreign body response to degradable P nanomeshes in vivo by altering the expression profile of mouse genes. eMSCs reduce acute inflammatory and increase ECM synthesis, angiogenesis and anti-inflammatory gene expression at 6 weeks while forming newly synthesized collagen within the nanomeshes and neo-vasculature in close proximity. From a tissue engineering perspective, this is a hallmark of a highly successful implant, suggesting significant potential as alternative surgical constructs for the treatment of POP.